SOCIAL AND PSYCHOLOGICAL FACTORS THAT INFLUENCE CONSCRIPTS ADAPTATION - Мозговий, Віктор Іванович (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2017)
The article presents research materials of socio-psychological factors that inﬂ uence psychological adaptation conscripts during the period of their educational training before taking the oath. There were found pivotal factors of socio-psychological impact on the adaptation of individual soldiers. A speciﬁ c factor that separates the military from civilian life is a factor of “organization mode of the day.”